Exploring the Significance of Storytelling and Retelling Activities in English Language Learning - Rifiyanti, Hafizah; Hidayat, Syamsu (Tamaddun Life, 2024)
The study aims to explore the effectiveness of using storytelling and retelling methods in improving students' English comprehension and proficiency. Through this activity, students were given the opportunity to listen to the story "Timun Mas" and then asked to retell the story in English according to their understanding. The study used qualitative method with convenience sampling. The participants are 40 students aged 6-10 years old from various schools in Srengseng Sawah. Data was collected through analyzing the answers of 40 students as well as the results of a questionnaire that measured students' understanding and response to the activity. The results showed that storytelling and retelling activities were effective in improving students' understanding of the story material, as well as developing their English language skills. Although there were variations in the level of understanding and command of English among the students, most of them were able to convey the essence of the story well, according to their own understanding. However, the evaluation results also highlighted some areas that need further attention, such as providing additional help to students who are having difficulties, as well as evaluating and refining the teaching methods used. Therefore, suggestions for future learning activities are to consider a variety of learning strategies that are more interactive and responsive, as well as to continue to encourage collaboration. The study offers insights and practical recommendations for educators to improve English language education by integrating storytelling and retelling activities into teaching practices. The approach not only improves students' language skills, but also fosters creativity, cultural understanding and critical thinking